2018
DOI: 10.1002/jmri.26027
|View full text |Cite
|
Sign up to set email alerts
|

LI‐RADS 2017: An update

Abstract: 5 Technical Efficacy: Stage 5 J. Magn. Reson. Imaging 2018;47:1459-1474.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…This complexity has resulted in the development of several staging algorithms, including RECIST, modified RECIST, and the Liver Reporting and Data System. Scores from these algorithms are frequently revised and are the focus of intense discussions (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…This complexity has resulted in the development of several staging algorithms, including RECIST, modified RECIST, and the Liver Reporting and Data System. Scores from these algorithms are frequently revised and are the focus of intense discussions (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of pretreatment nonmalignant lesions presents a challenge for hepatologists. The LI‐RADS criteria were developed to try and overcome this, but diagnostic uncertainty remains . We have shown that patients with apparently nonmalignant lesions on scans taken within 12 months of the onset of DAA therapy are more likely to go on to develop HCC.…”
Section: Discussionmentioning
confidence: 99%
“…All local imaging and multidisciplinary team (MDT) reports were collected centrally by the study team for the year prior to therapy and following therapy up until the study endpoint. Tumour size measurements were taken from radiological reports and Barcelona clinic liver cancer (BCLC) scores, Liver Reporting & Data System (Li‐RADS) grading, Milan criteria and response evaluation criteria in solid tumours (RECIST) criteria were applied and appropriate scores/grades generated by the study team. RECIST criteria, which take into account the size and progression of the primary lesion, secondary lesions, nodal, vascular and metastatic disease to give an overall definition for complete resolution, partial resolution, stable or progressive disease, were used to assess tumour progression with the date of cross‐sectional imaging being used to define the observation period.…”
Section: Methodsmentioning
confidence: 99%
“…Ancillary features also can be used to improve lesion detection or diagnostic confidence. Detailed discussion of ancillary features and tie-breaking rules can be found on the ACR website and in review articles (5,8,29).…”
Section: Ct/mri Techniquementioning
confidence: 99%